Strategic Integration of Artificial Intelligence: The Mediating Role of Dynamic Capabilities and Moderating Influence of Environmental Turbulence in Developing Economies - Fatmah Bagis; Maria Hasmi; Mega Aprillia Pratamasari; Ogun Prayoga; Zaki Nurhamam (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This research investigates how organizations in developing nations focusing on Indonesia can effectively embed Artificial Intelligence (AI) into their strategic operations to boost competitiveness and support the achievement of Sustainable Development Goals (SDGs). Drawing upon Dynamic Capability Theory (DCT) and the Technology-Organization-Environment (TOE) framework, the study examines the role of AI readiness in fostering strategic AI integration, with dynamic capabilities acting as a mediating mechanism and environmental turbulence serving as a moderating factor. A survey of 150 industry managers in Central Java was conducted, with data analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. Results indicate that organizations with higher AI readiness tend to develop stronger dynamic capabilities, which subsequently enhance their strategic integration of AI. Additionally, the study finds that environmental turbulence can amplify or diminish the influence of dynamic capabilities. Theoretically, the research extends the TOE framework by incorporating dynamic capability perspectives, while practically offering guidance for business leaders and policymakers aiming to implement AI in ways that are both effective and sustainable.